DEVELOPING ‘ELF COMPETENCE’ IN LANGUAGE LEARNERS AND TEACHERS - Blair, Andrew (Estudos Linguísticos e Literários, 2020)
‘Competence’ is a contested term, its definition for language learners and teachers challenged by the realities of lingua franca and translingual communication. Similarly, attitudes towards language standards, models, variability and change tend to condition responses to ELF-influenced ideas on pedagogy and teacher education. Educators play a key role facilitating shifts in understanding, enabling teachers to mediate a reconceptualised view of learner/user capability, progress and success inside and outside the classroom. This paper discusses the impact of ELF-aware course content and approach for experienced practitioners, aimed at developing ‘ELF competence’, and reflects on potential future directions.